(untitled) (Revista de Administração, 2010)
The innovation of products and processes is considered an essential condition for the competitiveness of companies. In this changing environment, people management is linked to the capacity to formulate programs and policies that take into account the quality of life in the workplace, based on a broad view of human beings across several dimensions, including the biopsychosocial and organizational aspects. This case study, which is descriptive and qualitative, analyses the critical elements of the management of the quality of life in the workplace, focusing on process innovations in the petrochemical sector in the Greater ABC Region (Brazil) from 2001 to 2006, in order to contribute an integrating view for studies on work and innovation. This setting was validated based on the concepts of Tidd, Bessant and Pavitt (1997) on the subject of innovative companies. With this validation, the researchers turned toward the investigation of the critical factors of the management of quality of life in the workplace, according to Limongi-França (2004). This comprises its concept, productivity, legitimacy, practices and values, the manager's profile and the new competence. The analysis of these critical factors of the management of quality of life in the workplace within an innovation environment enables one to highlight certain improvements, such as ergonomic benefits, team integration, environment protection and the reliability of the processes. On the other hand, the research emphasizes the persistent challenges facing innovation and people management, which are linked to the development of workers for new processes, and to the implantation of effective programs of participation and communication.